The CES-Translog: Specification and Estimation of a New Cost Function - Pollak, Robert A.; Sickles, Robin C.; Wales, Terence J. (The Review of Economics and Statistics, 1984)
Robert A. Pollak, Robin C. Sickles, Terence J. Wales, The CES-Translog: Specification and Estimation of a New Cost Function, The Review of Economics and Statistics, Vol. 66, No. 4 (Nov., 1984), pp. 602-607